ISOLASI DAN IDENTIFIKASI BAKTERI Vibrio sp. PADA KERANG KAPAH (Meretrix meretrix) DI KABUPATEN TRENGGALEK - Ihsan, Burhanuddin (Jurnal Harpodon Borneo, 2017)
Meretrix meretrix is one type of shellfish that are included in the bivalves that are filter feeders that live in the waters. Many bacteria that live in the estuary with high salinity in the range of 20-40 ppt one of which is the Vibrio bacterium. This research aims to determine the presence of Vibrio spp. bacteria in M. meretrix from Cengkrong Mangrove Eduwisata River, Trenggalek. The Isolation of Vibrio bacteria was conducted by streat plate method on selective media of TCBSA (Thiosulfate Citrate Bile Salt Sucrose Agar) and identify the Vibrio bacterium through the morphological and biochemical tests based Bergey's Manual of Systematic Bacteriology In Microbiology laboratory of Biology Faculty of Gadjah Mada University. The Result showed there are 7 isolates Vibrio spp. bacterias in M. meretrix they are isolate 1.1, 1.4, 1.7, 1.8. 5.3, 3.5, 2.6 PSBI Keyword: Meretrix meretrix, Vibrio, identification